Country Size and the Price of Tradeables: is There Any Relationship Beyond Wishful Thinking? - Andrea Mantovani; Gianpaolo Rossini; Paolo Zanghieri (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2002)
The existence of transport costs among countries makes pricesof tradables diverge. When the market structure is a differentiated oligopoly the prices of tradables increase as a country get larger and/orricher. In a framework of economies of scale-differentiation-monopolistic competition a less definite result can be found, since it all depends onthe level of transport costs and the degree of openess. First we go through some theoretical aspects of these different approaches. Then, we provide empirical tests that may be able todiscriminate among the two competing approaches. The results show that a relationship exists between size, percapitaincomes and prices of tradables in countries separated by some transport cost. As a country is larger prices are lower, yet they become higher if percapita income is higher.
Keywords: 330